Inequality and the Growth of Bad Jobs. (November 2013) - Vidal, Matt
The share of jobs that are low-skill declined by 15% from 1960 to 2005, yet low-wage jobs have made up an increasing share of total job growth over that period. Scholar Matt Vidal discusses how the manufacturing-based, nationally bound economy of the postwar years allowed employers to pay decent wages for low-skill jobs, but in today's postindustrial, internationalized economy, wage-based competition has returned with a vengeance.